Schwere und mittelschwere Hämophilie unter prophylaktischer Substitutions therapie - Herbsleb, M.; Abou-Hamdan, R.; Puta, C.; Donath, L.; Kobelt, R.; Stanek, F.-D.; Hilberg, T.; Gabriel, H. H. W. (Hämostaseologie, 2012)
Due to its influence on haemophilic arthropathy, the evaluation of knee extensor (KExt) and flexor (KFlex) torques plays an important role in the preventive and rehabilitative context of haemophilia. Thus, the present study aimed at investigating maximal static torque (MMax) of KExt and KFlex. 14 boys with haemophilia (8 severe, 6 moderate; age: 11.7 ± 2.8 years; prophylactic treatment > 5 years) and 14 healthy carefully pair-matched controls (age: 11.5 ± 2.7 years) were separately measured for the left and right leg for MMax. Furthermore, the ratio KFlex/KExt was calculated and the joint situation assessed using the Haemophilia Joint Health Score. Results: No significant group-effect was observed for MMax of the KExt and KFlex as well as for the ratio KFlex/KExt (p > 0.05). Despite significant higher joint scores in haemophilic children compared to their healthy controls (p < 0.01), patients merely showed minor joint impairments. Conclusion: Children and adolescents with severe and moderate haemophilia under prophylactic replacement treatment with a good joint status showed comparable maximal strength performance of relevant knee muscles compared to their healthy peers.
Keywords: Haemophilia; children; strength; quadriceps; hamstring muscle